ChemInform Abstract: Metal‐Free Fluorination of C(sp3)—H Bonds Using a Catalytic N‐Oxyl Radical. Issue 35 (8th August 2013) - Amaoka, Yuuki; Nagatomo, Masanori; Inoue, Masayuki
Abstract The simple reagent system composed of NDHPI (cat.) and Selectfluor enables a metal‐free fluorination under mild conditions.